Dendrimers and Antivirals: A Review - Rosa Borges, A.; Schengrund, C.- L. (Current Drug Targets - Infectious Disorders, 2005)
In response to the need for antiviral agents, dendrimers, hyper-branched, well-defined, and chemically versatile molecules, have been found to have a number of potential uses. How they are used is based on knowledge of 1) how a virus interacts with its target cells, 2) how it replicates, and 3) which viral components are recognized by the immune response of the host. Many viral-host cell interactions are initiated by viral proteins binding to specific cell surface carbohydrates. Dendrimers offer an efficient means of presenting multiple ligands, or sites of contact, on a single molecule. Derivatized with carbohydrate residues, the multivalent ligands have been shown to inhibit viral binding. Dendrimers derivatized with peptides or anionic groups have also been found to inhibit infection. The availability of a number of different types of dendrimers permits synthesis of potential inhibitors of viral binding to be tailored to meet the dimensions needed for optimum adherence by the virus. Future directions should see increased studies of the use of dendrimers as carriers of 1) multiple indicators on a viral probe to increase diagnostic sensitivity, 2) multiple peptides for use as immunogens or as inhibitors of viral binding, and 3) inhibitors of viral enzymes. While the field of dendrimer chemistry is relatively young, promising results indicate that dendrimers may provide the scaffolding needed for development of effective antivirals.
Keywords: multivalent ligands